Animaux à aimer, animaux à tuer - Damien Baldin (Revue d’Histoire des Sciences Humaines)
The purpose of this article is to shed light on the notion of “animality” and its ambivalent meaning (is animality what is shared by both humans and animals, or is it what negatively separates the latter from the former?) by tracing its historical background and development in the 19th century. During the 19th century, the notion was indeed largely discussed in France in the scientific world and by authors such as Balzac and Michelet. Its contemporaneity was reinforced by a social context, the relationship between men and animals enduring deep transformations at the time. The pet phenomenon and the agricultural expansion led to a strengthened intimacy and material familiarity with animals in city flats as well as farms. Furthermore, the birth of animal protection (creation of the Society for the Protection of Animals, adoption of the Grammont law prohibiting ill-treatments) amplified the idea that there should be some sort of natural and beneficiary proximity between men and animals. However the 19th century was also paradoxically the time of the development of public hygiene policies that chastised the promiscuity between humans and animals. The animal world was then put under a strict surveillance and linked to possible disciplinary measures, ranging from banishment to elimination. Thus the shaping of those spaces of death and internment such as slaughterhouses and dog pounds, where this animality that was judged unworthy of living with humans began to be put aside.